PENINGKATAN KEWASPADAAN DAN PEMAHAMAN GURU TERHADAP ETIKA PENULISAN KARYA ILMIAH (STUDI KASUS: SD NEGERI 4 KEDOYO KABUPATEN TULUNGAGUNG) - M. Mirza Abdillah Pratama; Christian Hadhinata; Kartika Indah Wahyuni; Ummi Afifatul Mufida; Syafa Aqilla Fadya; Julieta Eka Yudho Putri; Siti Nur Rahmah Anwar; Sri Umniati; Prijono Bagus Susanto; Lusty Mustikasari (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2022)
Writing scientific papers is one of the most significant things a teacher can do, especially if they want to advance to functional positions. However, producing scientific papers is a barrier for many teachers, leading to teachers engaging in dishonest behavior while writing scientific papers. The goal of this service is to organize socialization, training, and mentorship for SD Negeri 4 Kedoyo instructors on the importance of ethical issues and codes of ethics in scientific paper writing. This service's implementation is divided into three stages: pre-implementation, implementation, and post-implementation. As a result of this activity, socialization, training, and support in scientific writing with three primary resources, namely plagiarism, paraphrasing approaches, and reference managers, have been implemented. The post-test questionnaire score increased by 42.67% for the plagiarism indicator, 43.18% for the paraphrasing technique indicator, and 47.74% for the reference manager indicator, indicating an increase in SD Negeri 4 Kedoyo teachers' knowledge and understanding of literacy violations, ethics, and the code of ethics in writing scientific papers.